Infrared Dielectric Characteristics Of Porous Binary And Ternary Iii-Nitrides Heterostructures - Yew, Pauline (2018)
Porosity and composition dependence of infrared (IR) dielectric function of wurtzite III-nitrides are explored theoretically and experimentally. “Suspension-like” (i.e., porous GaN) and “solution-like” (i.e., InxGa1-xN) mixture are employed to investigate porosity and composition dependence of IR dielectric function respectively. Although many effective medium theories (EMTs) are available in literature, selection of appropriate EMT to describe the effective dielectric response for “suspension-like” mixture remains challenging and ambiguous. Therefore, an in-depth study on the effective dielectric properties for two-component mixtures which have four possible combinations of dielectric functions is performed. A comprehensive guideline for selecting the EMT to describe the effective dielectric behaviour of “suspension-like” mixture is proposed. Subsequently, polarized IR reflectance measurements of a set of porous GaN samples (PGaN) are performed to investigate the best EMT in describing the PGaN system as well as the impact of porosity on effective dielectric function. The reflectance spectra of PGaN can be fully described by factorized-Rayleigh (Ra) model which is developed for the first time to account for the damping of Fröhlich modes. Two weak Fröhlich modes are detected in the s-polarized IR reflectance spectra of PGaN at 710 cm-1 and 730 cm-1. This implies that two additional surface phonon polariton (SPhP) modes are expected to appear in p-polarized IR attenuated total reflection spectra of PGaN. Besides, a red shift of SPhP mode of PGaN with increasing porosity can be predicted using factorized-Ra model.